If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -8b + 6 + -2 = 0 Reorder the terms: 5 + 6 + -2 + -8b = 0 Combine like terms: 5 + 6 = 11 11 + -2 + -8b = 0 Combine like terms: 11 + -2 = 9 9 + -8b = 0 Solving 9 + -8b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -8b = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -8b = 0 + -9 -8b = 0 + -9 Combine like terms: 0 + -9 = -9 -8b = -9 Divide each side by '-8'. b = 1.125 Simplifying b = 1.125
| -x=2x-15 | | 5f+3B=5.70 | | (-8)^3/2 | | -34=-6x+3x+2 | | -2(x-3)=-3(2-4/3x) | | 16+4x(7+8)-3=65 | | 7(-5-x)=8(-13) | | 9k-(5k-14)= | | 1=3-3z | | (8X-2)+(3-5X)=(X-3) | | x-4/6=×/2 | | 6x-3=-2x+21 | | 5x+3+3x=-77 | | 5/8^ | | 10p-3=2(12+8p)-7 | | 18x-x^2-3x^3-6=0 | | 9/4*5/8 | | g(x)=f(-4x) | | 25.2/-.4 | | 4*5/8-1/4 | | 10p-3=2(12+p)-7 | | p^2+4*p+2=0 | | (k-1)x*x+4k-1=(3+4k)x | | x=-7/2 | | 6(2a-5)=7a+19 | | (y-7)(y-5)(y-2)=0 | | 112/5/4/5 | | 5x-2(2x-3)=10 | | 112/5= | | 2x-3x-5x=10+4-8 | | 24-8/5 | | w/-7=-2.4 |